Anodizing and inorganic black coloring of aluminum alloys for space applications - Sharma, A.K.; Bhojraj, H.; Kaila, V.K.; Narayanamurthy, H. (Metal finishing, 1997)
Aluminum anodizing is the subject of intensive research because of its immense technological importance in the aerospace, building, and electronics industries. The studies reported in this article are aimed at developing a simple process of anodizing and inorganic black coloring for aerospace applications. Process optimization was carried out by investigating the influence of various operating parameters such as voltage, current density, electrolyte temperature, electrolyte concentration, anodic coating thickness, and concentration of inorganic coloring salts on the physio-optical properties of the coating. Experiments were conducted on aluminum alloys 1100, 2024 and 6061.